Analysis of poly(dioxanone) foam prepared using salt leaching method. Issue 24 (11th March 2022) - Kim, Jung Min; Kyung, Haksu; Song, Young Seok
Abstract: This study aims at preparing and analyzing porous biodegradable polymer foam. Poly(dioxanone) (PDO) foams with a three‐dimensional structure and high porosity were fabricated by using sodium chloride (NaCl) particulate leaching method. The influence of the size composition of PDO and NaCl was investigated to understand the relationship between polymer matrix and salt during the manufacturing process. The physical characteristics of the prepared foam, such as moldability, leaching state, porosity, permeability, swelling ratio, pore density, and mechanical property were analyzed. The PDO foams with high dimensional stability were prepared when the PDO particles were smaller than the NaCl particles, and the porosity of the PDO foam increased with decreasing the particle size of PDO. In addition, the compression modulus of the foam was analyzed to estimate a possibility for application in tissue engineering. Abstract :